Modulation of Gut Microbiome Composition and Function in Experimental Colitis Treated with Sulfasalazine - Zheng, Haihui; Chen, Mingyi; Li, Yuan; Wang, Yuanyuan; Wei, Lin; Liao, Ziqiong; Wang, Mengxia; Ma, Fangli; Liao, Qiongfeng; Xie, Zhiyong (Frontiers in Microbiology, 2017)
Inflammatory bowel disease (IBD) results from alterations in intestinal flora and the immune system. Sulphasalazine (SASP) is a sulfa antimicrobial used to treat IBD in clinic for years. However, how SASP affects gut microbes and its potential functions remains unclear. To investigate the relationships of SASP, IBD and gut microbiome, we used 2,4,6-trinitrobenzenesulfonic acid (TNBS) to induce experimental colitis in rats, and analyzed the microbiota in the fecal samples, which come from the control group (treated with ethanol + saline), the model group (treated with TNBS-ethanol + saline) and the SASP group (treated with TNBS-ethanol + SASP), with 16S gene sequencing and followed up a subset sample using shotgun sequencing. The study found that SASP treatment could not only restore the TNBS-induced gut dysbiosis, which was proved by the increasing amount of SCFAs-producing bacteria and lactic acid-producing bacteria as well as the decreasing amount of Proteobacteria, but also modulate the dysregulated function of the TNBS-induced colitis to resemble that of the control group, including an increased capacity for basic metabolism (carbohydrate metabolism, citrate cycle) and a decrease in the oxidative stress (riboflavin, sulfur, cysteine) as well as bacterial pathogenesis (cell motility and secretion, bacterial motility proteins, flagellar assembly). Moreover, a higher proportion of Mycoplasma was observed in the SASP group, which may associate with infertility. In all, the study provides insight into specific microbial clades and pathways linked with SASP treatment to elaborate the mechanism for treatment of IBD.